PENGARUH RASIO CAMEL TERHADAP KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DI INDONESIA PERIODE 2010-2012 - Dinny Marwati; Tina Sulistiyani (Universitas Ahmad Dahlan, 2014)
This research is aimed to analyze and assess the effect of CAMEL ratio on the financial performance of Regional Development Banks in Indonesia. The independent variables used were Capital Adequancy Ratio (CAR), Non-Performing loans (NPL), Net Profit Margin(NPM), Return On Asset(ROA), and Loan to Deposit Ratio(LDR). Meanwhile, the dependent variable was financial performance viewd from the profit growth of the banks. Based on the result of the research, it is determined that partially, only ROA variable which significantly affects the Financial Performance of the Regional Development Banks in Indonesia. Whilst CAR, NPL, NPM, and LDR variables do not affect significantly on the financial performance of the Regional Development Banks in Indonesia. Simultaneous test result shows that CAR, NPL, NPM, ROA and LDR variables have an effect on the financial performance of the Regional Development Banks in Indonesia. The amount of coefficient of determination is 53.22%.